Acute Promyelocytic Leukemia in a 17yr Male presenting as Intracerebral Haemorrhage (Bangladesh Journal of Medical Science, 2013)
Acute promyelocytic leukemia (APML), once highly fatal, has emerged as the most curable subtype of acute myeloid leukemia in adults. Early mortality most often is due to a severe catastrophic bleeding, often intracerebral in location. Here we report a 17year male patient presented with status epilepticus having high leukocyte count (3,28,000/mm3) and low platelet count(34,000/mm3).Peripheral blood & bone marrow was showing good no. of atypical promyelocytes. CT scan of brain revealed an intracerebral haemorrhage with laboratory profile of prolonged prothrombin time and activated partial thromboplastin time, the presence of Ddimer and decreased fibrinogen concentration. The patient was diagnosed as Acute Promyelocytic Leukemia with Intracerebral haemorrhage. The patient died on the same day. APML is the notorious subtype of acute myeloid leukemia which causes fatal intracranial haemorrhage which has high mortality and morbidity. Clinically significant coagulopathy is present in 70% 80% of APML patients at the time of diagnosis. Early detection and aggressive correction of coagulopathy may prevent the catastrophic event. Prompt image study for locations and types of ICH can predict outcomes. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14482 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 88-90